2010
DOI: 10.1063/1.3493330
|View full text |Cite
|
Sign up to set email alerts
|

Curvature effects upon interactions of polymer-grafted nanoparticles in chemically identical polymer matrices

Abstract: We study the interactions between polymer-grafted nanoparticles immersed in a chemically identical polymer melt using a numerical implementation of polymer mean-field theory. We focus on the interpenetration width between the grafted and free chains and its relationship to the polymer-mediated interparticle interactions. To this end, we quantify the interpenetration width as a function of particle curvature, grafting density, and the relative molecular weights of the grafted and free chains. We show the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(157 citation statements)
references
References 57 publications
11
146
0
Order By: Relevance
“…22,24,26,33,37,42,50,88,90,95,109,[119][120][121][122]125,[143][144][145][146][147][148][149][150] Ganesan et al 22 have shown that the morphologies adopted by grafted NPs in a selective solvent are sensitively determined by the ratio of the NP core size to the native size of the polymeric grafts. Recent work by Jayaraman, 88,89,92 which is in good agreement with experiments, illustrates that the polydispersity of graft lengths can play a critical role in the miscibility of NPs in a polymer matrix with the same chemistry as the brush.…”
Section: Grafted Nanoparticlesmentioning
confidence: 99%
“…22,24,26,33,37,42,50,88,90,95,109,[119][120][121][122]125,[143][144][145][146][147][148][149][150] Ganesan et al 22 have shown that the morphologies adopted by grafted NPs in a selective solvent are sensitively determined by the ratio of the NP core size to the native size of the polymeric grafts. Recent work by Jayaraman, 88,89,92 which is in good agreement with experiments, illustrates that the polydispersity of graft lengths can play a critical role in the miscibility of NPs in a polymer matrix with the same chemistry as the brush.…”
Section: Grafted Nanoparticlesmentioning
confidence: 99%
“…The cumulative mass distributions, shown in the inset to Figure 3, are almost identical for all matrix molar masses. Since R n /R g > 1, the theory of Trombly and Ganesan 65 predicts that the "wet to dry" transition should occur for N f /N g < 1. This requirement would be fullfilled by studying even shorter matrix chains.…”
Section: Influence Of Grafted Chain Molar Massmentioning
confidence: 99%
“…Indeed, recent SCF calculations have shown that wetting-dewetting transition is shifted to much larger values of P/N ratio for highly curved sterically stabilized nanoparticles. [21] This change in the nature of the lock-key PMF from attractive to repulsive with increasing volume fraction (when P > N ) provides one possible way for tuning interactions in sterically stabilized lock-key colloidal systems. Hence, it would be of interest to decompose the total polymer-induced PMF according to Eq.…”
Section: Resultsmentioning
confidence: 99%